Non-thermal alloyed ohmic contact process of GaN-based HEMTs by pulsed laser annealing. (15th March 2016) - Tzou, An-Jye; Hsieh, Dan-Hua; Chen, Szu-Hung; Li, Zhen-Yu; Chang, Chun-Yen; Kuo, Hao-Chung
Abstract: We have demonstrated Si implantation incorporation into GaN HEMTs with a non-alloyed ohmic contact process. We optimized the power density of pulsed laser annealing to activate implanted Si dopants without a thermal metallization process. The experimental results show that the GaN surface will be reformed under the high power density of the illumination conditions. It provides a smooth surface for following contact engineering and leads to comparable contact resistance. The transmission line model (TLM) measurement shows a lower contact resistance to 6.8 × 10 −7 Ω · cm 2 via non-alloyed contact technology with significantly improved surface morphology of the contact metals. DC measurement of HEMTs shows better current and on-resistance. The on-resistance could be decreased from 2.18 to 1.74 mΩ-cm 2 as we produce a lower contact resistance. Pulsed laser annealing also results in lower gate leakage and smaller dispersion under a pulse I-V measurement, which implies that the density of the surface state is improved.